2019
DOI: 10.1002/2211-5463.12694
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the human gut microbiome associated with Helicobacter pylori infection

Abstract: Helicobacter pylori infection ( HPI ) is a prevalent infectious disease associated with gastric ulcer, gastric cancer, and many nongastrointestinal disorders. To identify genes that may serve as microbial markers for HPI , we performed shotgun metagenomic sequencing of fecal samples from 313 Chinese volunteers who had undergone a C14 breath test. Through comparing differences in intestinal microbial community structure between H. pylori … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 32 publications
(55 reference statements)
2
33
0
Order By: Relevance
“…Similar results were also reported for studies carried out with American and Swedish dyspeptic individuals [ 5 , 34 ], which confirmed that an H. pylori infection alters the gastric physiology and would be more likely to affect the gastric microbiota [ 15 , 31 , 32 , 49 , 50 , 51 ]. Our work confirmed that few culturable species persisted in the malignant epithelium.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar results were also reported for studies carried out with American and Swedish dyspeptic individuals [ 5 , 34 ], which confirmed that an H. pylori infection alters the gastric physiology and would be more likely to affect the gastric microbiota [ 15 , 31 , 32 , 49 , 50 , 51 ]. Our work confirmed that few culturable species persisted in the malignant epithelium.…”
Section: Discussionsupporting
confidence: 86%
“…Conversely, Proteobacteria, Actinobacteria, and Firmicutes phyla were also identified in the HP+ group showing significantly less abundance (number of species identified from each phylum), even when including participants who had taken an eradication treatment in the HP- group ( p = 0.031, Tables S1 and S2 ). The results mentioned above highlight that bacteria diversity decreases in people infected with H. pylori , and might be recovered after eradication treatments, as reported in similar studies [ 15 , 31 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 78%
“…The most consistent findings were for Fusobacterium (with most important species Fusobacterium nucleatum), Parvimonas, Porphyromonas, and Peptostreptococcus, which were significantly enriched in both fecal and mucosal samples of patients with colorectal cancer compared with controls across multiple studies. Several of our reviewed articles and a recent metaanalysis (119) reported that Fusobacterium nucleatum, already known as an invasive and proinflammatory agent that can cause acute and chronic oral and gastrointestinal infections, was significantly enriched in both fecal and biopsy samples of colorectal cancer patients. With its unique FadA adhesin, Fusobacterium nucleatum adheres to, invades, and induces inflammatory and oncogenic responses to stimulate growth of colorectal cancer cells (120).…”
Section: Discussionmentioning
confidence: 99%
“…The other topic which deserves more attention is HPI-associated dysregulation of gut microbiota [ 239 , 606 , 653 , 654 , 655 , 656 , 657 , 658 , 659 , 660 , 661 , 662 , 663 , 664 , 665 , 666 , 667 ], a phenomenon described also in animal models (infected Mongolian gerbils [ 668 ]) and thought to be due mainly to gut immunopathological/inflammatory responses and suppressed gastric acid secretion following chronic/atrophic gastritis or use of acid-suppressive drugs. Gut dysbiosis by affecting various biological processes contributes to the pathogenesis of OP [ 669 , 670 , 671 , 672 , 673 , 674 , 675 , 676 , 677 , 678 , 679 , 680 , 681 , 682 , 683 , 684 , 685 , 686 , 687 , 688 , 689 , 690 , 691 , 692 , 693 , 694 , 695 , 696 , 697 , 698 , 699 ] as well as to numerous other extra-digestive system diseases associated with OFs [ 700 , 701 , 702 ,…”
Section: Clinical Implications and Recommendationsmentioning
confidence: 99%